Oral anticoagulation therapy with rivaroxaban in elderly patients with atrial fibrillation. Results from EMIR study. (14th October 2021) - Esteve Pastor, M; Marin, F; Anguita, M; Sanmartin, M; Rafols, C; Roldan, V; Perez, C; Barrios, V; Lekuona Goya, I; Perez Cabeza, A; Cosin Sales, J; ,
Abstract: Background: Atrial fibrillation (AF) in elderly patients increases both bleeding and thromboembolic risks. Elderly patients benefit as much from anticoagulation therapy with positive net clinical benefit. However, there have been few studies that focused on the efficacy and safety of direct oral anticoagulants in elderly patients. The aim of this subanalysis from EMIR study was to assess the effectiveness of rivaroxaban in patients older than 75 years old. Methods: EMIR Study (acronym from 'Estudio observacional para la identificaciόn de los factores de riesgo asociados a eventos cardiovasculares Mayores en pacientes con fIbrilaciόn auricular no valvular tratados con un anticoagulante oral directo (Rivaroxaban)') was an observational, multicenter, post-authorization and prospective study that involved AF patients under oral anticoagulation with rivaroxaban at least 6 months before enrolment. We analyzed baseline clinical characteristics and adverse events after 2.5 years of follow up. Results: We analyzed 1, 433 patients with median age of 74.7 (67.7–81.6). Of them 691 (48.2%) were ≥75 years. Elderly patients had higher prevalence of cardiovascular risk factors such previous stroke (16.8% vs 8.5%; p<0.001), heart failure (25.0% vs 20.6%; p<0.001), higher CHA2DS2-VASc (4.4±1.3 vs 2.7±1.2; p<0.001) and HAS-BLED (1.9±1.0 vs 1.2±1.0; p<0.001) scores. After 2.5 (2.2–2.6) years of follow-up, we observed low rate of adverse events in patients under rivaroxaban therapy. We observed higher rate of adverse events in elderly population for thromboembolic events (1.13%/year vs 0.36%/year; p=0.017) and major bleeding events (1.80%/year vs 0.36%/year; p<0.001) but those adverse rates were lower than expected according to previous studies (i.e. ROCKET-AF trial, rivaroxaban group had 4.86%/year of major bleeding or in XANTUS study was 3.2%/year of major bleeding in patients >75 years). We did not observe differences between groups from MACE (1.13%/year vs 1.01%/year; p=0.875) or cardiovascular death (0.86%/year vs 0.42%/year; p=0.170). Conclusion: In real-world elderly population, rivaroxaban showed higher rates of thromboembolic and major bleeding events in elderly patients but with annual rates lower than expected according to previous studies like ROCKET-AF or XANTUS. Similar annual rates in elderly were observed for MACE and cardiovascular mortality than in younger patients, being rivaroxaban a good therapeutic alternative even for the elderly. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Bayer Hispania S.L.